Implementation of Renewable Energy Policy: A Case Study of Solar Panel Electricity on DPR RI - Waluyo; Tjenreng, M. Baharudin Zubakhrum (GoAcademica Research & Publishing, 2025)
The implementation of renewable energy policies in public institutions is crucial to achieving national energy transition goals. This study examines the solar rooftop photovoltaic (PV) project at the Indonesian House of Representatives (DPR RI) as a concrete example of policy realization. Through a qualitative case study approach, supported by document analysis and literature review, the research analyzes how the DPR project operationalizes Presidential Regulation No. 22/2017, which mandates the use of solar panels on at least 30% of government building rooftops. The project, implemented via a public-private partnership, achieved an installed capacity of 1.955 MWp, supplying approximately 25% of the DPR’s electricity demand and generating annual savings of over Rp 4 billion. It also contributes to national emissions reduction by avoiding more than 2,000 tons of CO₂ annually. The findings highlight the effectiveness of leadership-by-example strategies, the role of supportive regulations (such as net metering), and the viability of innovative financing models in overcoming barriers to renewable energy adoption. This case underscores the importance of consistent policy frameworks and suggests replicability across other government institutions as a key strategy for accelerating Indonesia’s renewable energy transition.